PREDICTION OF THE AMOUNT OF PEPPER HARVEST BY USING FUZZY ASSOCIATIVE MEMORY - Ipung Permadi; Arief Kelik Nugroho; Maghfira Rosnadila Rachmat (Informatika, Universitas Jenderal Soedirman, 2022)
Prediction of pepper data is done by looking at several variables to get optimal results. From the production data of the pepper harvest, the information is not yet available to farmers. By using the fuzzy method, the author tries to create a system to estimate the results of predictions by considering the parameters of the number of seeds, fertilizers, pesticides and labor. The combination of these variables can produce an intelligent system that is able to learn and adapt to environments with incomplete and precise data variations and fuzzy logic that has the ability to translate expert knowledge by using linguistically constructed rules. From the results of the experiments conducted, the results obtained were 900 kg of production data.